Electroactive polymers synthesis and applications - Muralisrinivasan, Natamai Subramanian (De Gruyter, 2021)
"The book focuses on the development of high performance, high efficiency electroactive polymers (EAPs), and electromechanically active polymers by controlling molecular chemical structure and morphology for all applications. This book is ideal for academicians and researchers in polymer and materials science"--